Upaya Perbaikan Pertumbuhan Tanaman Jabon (Anthocephalus Cadamba) Dengan Pemberian Pupuk Kompos Kotoran Sapi Pada Beberapa Ketinggian Tempat - Agus Wahyudi; Indriyanto Indriyanto; Melya Riniarti (Jurnal Sylva Lestari, 2014)
Kadam is one of short rotation plant species because it has a rapid growth. Kadam does not require special treatment to maintenance. General plant maintenance in the early planting was fertilizer. The organic fertilizer such as cow manure compost which added to soil could increase the nutrients substance. The objectives of this research to know the effect of cow manure compost, the best dosage of cow manure compost, and the best altitude for kadam growth. The research was conducted on June - October 2012 at community plantations forest area in West Lampung. The research was arranged in the Block Randomized Design (BRD) with 3 block and 6 treatment. The altitude as block were 124 m, 118 m, and 116 m above sea level. The dosage cow manure compost as treatment were 0 kg/plant, 2 kg/plant, 3 kg/plant, 4 kg/plant, 5 kg/plant, and 6 kg/plant. Bartlett test, analysis of variance, and least significant difference at 5% level were used to analysis of this data. The results of this research showed that dosage of cow manure compost had no significant effect on all variables. Where as the altitude had effect on numbers of leaves only. Keywords: altitude, cow manure, fertilizer, kadam